An Image Encryption Algorithm Based on Josephus Traversing and Mixed Chaotic Map - Wang, Xingyuan; Zhu, Xiaoqiang; Zhang, Yingqian (IEEE access, 2018)
This paper proposes a new chaotic image encryption scheme, which employs Josephus traversing and mixed chaotic map. The scheme consists of three processes: key stream generation process; three-round scrambling process; and one-round diffusion process. The proposed mathematical model is applied for the key stream generator in the first process. The initial values and parameters are sensitive to both the secret keys in the new scheme and plain images. The second process employs the Josephus traversing in scrambling; then the rows and columns of pixels are exchanged. The third process can modify the pixel gray-level values and crack the strong correlations between adjacent pixels simultaneously. The initial conditions for chaotic systems are derived using external secret keys by applying some algebraic transformations to the key. Security analysis indicates that the new scheme is effective, which can resist common attacks.